Lehninger principles of biochemistry - Lehninger, Albert L.; Nelson, David L. (David Lee), 1942-; Cox, Michael M.; Hoskins, Aaron A. (New York, NY : Macmillan Learning, 2021)
"Lehninger Principles of Biochemistry earned acclaim for its presentation and organization of complex concepts and connections, anchored in the principles of biochemistry. This legacy continues in the eighth edition with a new framework that highlights the principles and supports student learning"--
Revised edition of: Lehninger principles of biochemistry / David L. Nelson, Michael M. Cox. Seventh edition. [2017].
Includes bibliographical references and index.
PHR
Keywords: Biochemistry; Biochemistry -- Problems, exercises, etc